Narrative Functions of Ecology in The Novel Aroma Karsa by Dee Lestari - Ahmad Jum’a Khatib Nur Ali; Retno Budi Astuti (English Department, Faculty of Humanities, Andalas University, 2020)
Nature and Literature have a related meaning relationship. Ecological aspects paradigmatically can have a role in telling the story of literary works. This study aims to determine the narrative functions of ecology in the novel Aroma Karsa. The method of this study is a narrative analysis with a literary ecology approach in the ontological, epistemological and axiological scope focusing on the characters’ narrative functions. The data are obtained through the documentation process, which is in-depth reading; with the aim of identifying, classifying and categorizing the story based on the concept of the narrative function by Vladimir Propp. The results of the study identify four characters who ontologically have a strong relation to the ecological aspects of the story, namely; Sangyang Batari Karsa/Puspa Karsa, Jati Wesi/Randu, Tanaya Suma/Malini, and Raras Prayugung. Epistemologically, it is known that Aroma Karsa (1) builds perception of the cultural environment and ideal environmental criteria, and (2) enriches the ecological knowledge of the readers. Axiologically, Aroma Karsa mutually reveals the symbolic relationship of nature with the readers’ cultural receptions related to myths, medications, fragrances, gender and cleanliness. There are 5 spheres of action (villain, hero, helper, false hero, princess) out of 7 with 24 supporting functions on 4 identified characters. The mechanism of narrative function uses special personage in the form of character condensation to convey the premise of the story. The mechanism of the narrative function is centered on Puspa Karsa who becomes the symbol of ecocentric narrative in the novel Aroma Karsa.